An analysis of the effects of the variety of items on the retailer's market areas and the urban system - Toshiharu Ishikawa (European Regional Science Association (ERSA), 2013)
Due to the reduction of the transportation cost, the retailers become to be able to deal with many kinds of goods and to increase the number of items stocked at the stores. Corresponding to the increase of items stocked at stores, the customers tend to increase to visit the retailer that provides the more verities of goods. Hence, besides of the price of goods, the number of items at a store influences not only the retailerfs profits and its market area situation. Firstly, this paper incorporates the number of items into the traditional market analyses and it examines the effects of the number of items at a store on the shape of the market area boundary and it shows how the increase of the number of items alters the market area boundary. Secondly, dividing the retailersf stores into the three categories, convenience store, supermarket store, and department store, the paper derives the number of items, the average price of the retailing goods and the market area of a retailer in spatial free-entry equilibrium. It is also shown in this analysis that in the category of the convenience stores, the number of items at a store decreases and itfs the market area shrinks as the transportation costs reduce, while, in the categories of the supermarket stores and the department stores, the number of items at a store increases and their market areas expands due to the reduction of transportation costs. The fact that the reduction of the transportation costs expands the necessitated size of the market area for a retailer to survive in the market field is crucially important to the retailing structure of the urban system. Because the decreasing transportation costs expel some of department stores from the middle sized cities and thus damage the tertiary function of these cities. It causes the medium citiesf economic activity decay. As a result, many urban systems become to be formed by one large city and many small cities. This obtained result is supported by an empirical analysis using the recent Japanese data. The conclusions derived in this paper seem to be worth studying by detail methods.
Keywords: R30; 330; MARKET AREA; NUMBER OF ITEMS; SPATIAL FREE-ENTRY EQUILIBRIUM; URBAN SYSTEM